THE TEACHING STRATEGIES TOWARD STUDENTS’ DEVELOPMENT REFLECTED IN HARRY POTTER AND THE CHAMBER OF SECRET FILM - Ika Oktavia; Dwi Ario Fajar (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2022)
Learning is used to achieve a goal for both teachers and students. The successful learning depends on the teachers in delivered the materials which may engaged the student’s curiosity by using learning strategy. Learning strategy facilitate the learners to learn the material which make the learning process becomes easier, enjoyable and more effective. In fact, there are several ways to teach such as scaffolding and cooperative as strategies which may give the effect for the students especially in their cognitive development based on constructivism theory. The finding shows some strategies and its effect that used in the characters. Moreover, this research uses qualitative method to give a brief explanation and describing the problem. This research explains about the learning strategy that reflected in “Harry Potter and the chamber of secret” film which can inspire the teachers about the kinds of strategies and its effects that use in the film